Association between serum uric acid and chronic kidney disease in patients with hypertension: A multicenter nationwide cross‐sectional study. Issue 4 (4th September 2019) - Kaewput, Wisit; Thongprayoon, Charat; Rangsin, Ram; Ruangkanchanasetr, Prajej; Bathini, Tarun; Mao, Michael A.; Cheungpasitporn, Wisit
Abstract: Introduction: Current data on the role of hyperuricemia as a risk factor for renal progression in patients with hypertension is inconclusive. This study aimed to assess the association of uric acid and chronic kidney disease (CKD) in hypertensive patients using a nationwide patient sample. Methods: We conducted a nationwide cross‐sectional study based on the DM/HT study of the Medical Research Network of the Consortium of Thai Medical Schools. This study evaluated adult patients with hypertension from 831 Thailand public hospitals in the year 2014. Serum uric acid (SUA) was categorized into quintiles (≤4.5, 4.6 to 5.4, 5.5 to 6.2, 6.3 to 7.4, ≥7.5 mg/dL). CKD was defined as estimated glomerular filtration rate of ≤ 60 mL/min/1.73 m 2 . Multivariate logistic regression was performed to assess the association between SUA and CKD using uric acid of ≤4.5 mg/dL as the reference group. Results: A total of 9776 hypertensive patients with available SUA were included in the analysis. The mean SUA was 6.1±1.8 mg/dL. The prevalence of CKD in hypertensive patients was 31.8%. SUA of 4.6 to 5.4, 5.5 to 6.2, 6.3 to 7.4, and ≥7.5 mg/dL were associated with an increased CKD with ORs of 1.57 (95% CI 1.28 to 1.92), 2.15 (95% CI 1.74 to 2.66), 3.31 (95% CI 2.72 to 4.04), and 7.11 (95% CI 5.76 to 8.78), respectively. The restricted cubic spline showed significant increased CKD prevalence when uric acid ≥4.6 mg/dL. Conclusion: Higher SUA was associated with increased CKD prevalence in patients with hypertension. SUA should be monitored in hypertensive patients for CKD prevention.